2014
DOI: 10.5194/isprsarchives-xl-5-589-2014
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring marginal erosion in hydroelectric reservoirs with terrestrial mobile laser scanner

Abstract: ABSTRACT:Marginal erosions in reservoirs of hydroelectric plants have caused economic and environmental problems concerning hydroelectric power generation, reduction of productive areas and devaluing land parcels. The real extension and dynamics of these erosion processes are not well known for Brazilian reservoirs. To objectively assess these problems Unesp (Univ Estadual Paulista) and Duke Energy are developing a joint project which aims at the monitoring the progression of some erosive processes and underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 13 publications
(12 reference statements)
0
11
0
Order By: Relevance
“…The light weight of these MLSs makes them flexible and versatile instruments, so they can be mounted on any mobile platform. In places with complex topography, the use of MMS, following a continuous path, is more advantageous than a tripod-based laser scanner that requires multiple scan positions to cover all the areas of the survey [6]. Moreover, integrating MMS with other geomatics techniques, such as Digital Photogrammetry (DP), allows giving an added value and greater richness of the acquired data providing a high detailed DEM or DTM (Digital Terrain Model) of the selected area [8].…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…The light weight of these MLSs makes them flexible and versatile instruments, so they can be mounted on any mobile platform. In places with complex topography, the use of MMS, following a continuous path, is more advantageous than a tripod-based laser scanner that requires multiple scan positions to cover all the areas of the survey [6]. Moreover, integrating MMS with other geomatics techniques, such as Digital Photogrammetry (DP), allows giving an added value and greater richness of the acquired data providing a high detailed DEM or DTM (Digital Terrain Model) of the selected area [8].…”
Section: Related Workmentioning
confidence: 99%
“…A boat-based MMS was selected by Brazilian researchers to scan the progression of marginal erosion in different reservoirs of hydroelectric plants. The processed point clouds and rendered meshes and the creation of cross-sections were used to compute the rate and the dynamics of the erosion phenomenon [6,22].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The hydroelectric plant reservoir is formed by the Paranapanema River, which creates the border of São Paulo and Paraná States. The reservoir has an area of approximately 400 km 2 with a perimeter of 1085 km [15]. Hundreds of eroded regions can be identified on the banks of the reservoir.…”
Section: A Experiments 1-boat-based Laser Scanning Accuracy Assessment In the Chavantes Hydroelectric Plant Test Fieldmentioning
confidence: 99%
“…In order of relevance, the paramount role is taken by terrestrial laser scanning (TLS) (see for example, Bitelli et al (2004), Guffar et al (2013), and Barbarella et al (2014)). A few experiences with laser scanning systems implemented in terrestrial mobile vehicles (mobile laser scanning-MLS) have been also reported in De Agostino et al (2012) and Tommaselli et al (2014). The advantage of laser scanning techniques is they may directly provide a dense point cloud describing the topographic ground or vertical rock faces (see Abellán et al (2014)).…”
Section: Introduction: Remote Sensing For Landslide Investigationsmentioning
confidence: 99%